Evaluation of the effect of handheld mobile phone use on activity of the parotid glands amylase enzyme - Neda Babaee; Hamed Kazemi; Seyed Ali Asghar Sefidgar; Ali Bijani; Mehdi Pouramir; Hadi Mortazavi; Nafiseh Ghasemi (Babol University of Medical Sciences, 2016)
Introduction: Alpha amylase is the most abundant enzyme of parotid gland. This enzyme starts digestion of carbohydrates in the mouth. A pair of parotid glands is located in front of ears. Several studies have been conducted on the effects of mobile phones on the parotid gland. The aim of this study was to investigate the effects of mobile phones on the activity of the amylase enzyme. Materials &Methods: Totally, 251 men and women aged 18 to 55 years, who only used Hamrahe Aval's operator were included. Parotid salivary samples of each individual were bilaterally collected using capillary tube placed in the vicinity of Stensen's duct. Bilateral amylase activity of each individual was evaluated with spectrophotometric method in the laboratory considering dominant sides of phone conversation and chewing. Data were analyzed using Two-way ANOVA, χ2, T test and SPSS software. Results: The relationship between the dominant phone conversation side and parotid amylase activity was not statistically significant but the correlation between prevailing chewing side and amylase activity was statistically significant (p=0.001). Conclusion: Handheld mobile phone was not effective on parotid amylase enzyme activity whereas chewing was effective on parotid amylase enzyme activity.